2007
DOI: 10.1037/0022-3514.92.5.871
|View full text |Cite
|
Sign up to set email alerts
|

Vengefully ever after: Destiny beliefs, state attachment anxiety, and forgiveness.

Abstract: Two studies examined how destiny beliefs (that potential relationships are or are not "meant to be") interact with state attachment anxiety to predict forgiveness tendencies. In Study 1, participants experienced an experimental manipulation of attachment anxiety (vs. security) before indicating the degree to which they would forgive a series of hypothetical partner offenses. In Study 2, participants reported every 2 weeks for 6 months (14 waves in total) on offenses enacted by their partner and indicated the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 92 publications
3
84
0
1
Order By: Relevance
“…Fifth, implicit theories in a quantifiable form (e.g., assessed with a self-report instrument, experimentally induced) and at least one of the six self-regulatory processes or an achievement outcome, as established by the SOMA Model, must have been included. We excluded findings and articles focusing on implicit theories of relationships (e.g., Finkel, Burnette, & Scissors, 2007; 1 If data from any unpublished manuscripts were published before this article was accepted for publication, we updated effects and references to include the most recent findings.…”
Section: Methods Search Strategy and Inclusion Criteriamentioning
confidence: 99%
“…Fifth, implicit theories in a quantifiable form (e.g., assessed with a self-report instrument, experimentally induced) and at least one of the six self-regulatory processes or an achievement outcome, as established by the SOMA Model, must have been included. We excluded findings and articles focusing on implicit theories of relationships (e.g., Finkel, Burnette, & Scissors, 2007; 1 If data from any unpublished manuscripts were published before this article was accepted for publication, we updated effects and references to include the most recent findings.…”
Section: Methods Search Strategy and Inclusion Criteriamentioning
confidence: 99%
“…Between completing the SDT need fulfillment measures and the commitment measure, we randomly assigned participants to experience either the attachment anxiety prime or the attachment security prime (see Finkel et al, 2007). Based on the scrambled sentence test priming procedure from the social cognition literature (Srull & Wyer, 1979; see Bargh & Chartrand, 2000), participants were presented with 10 different series of 5 words.…”
Section: Methodsmentioning
confidence: 99%
“…However, a substantial literature has emerged in recent years demonstrating that attachment representations vary not only across people (at the trait level) but also within a given person (at the state level). For example, daily diary studies have revealed considerable within-person fluctuation in attachment representations over time (e.g., Davila & Sargent, 2003), and laboratory studies in the social cognitive tradition demonstrate that attachment representations can be primed experimentally (e.g., Finkel, Burnette, & Scissors, 2007;Green & Campbell, 2000;Mikulincer, Shaver, Gillath, & Nitzberg, 2005). Thus, as a secondary issue in the present report, we test the hypothesis that stable and context-sensitive attachment representations function similarly in predicting relationship commitment, such that high levels of either stable or context-sensitive attachment anxiety predict individuals' sustained commitment when their partner fails to help fulfill their needs, while low levels do not.…”
Section: Attachment Anxiety and Sustained Dedication To An Unfulfillimentioning
confidence: 99%
“…Research has shown that lay theories substantially influence goaldirected behaviors across domains as diverse as academics, relationships, and New Year's resolutions (Finkel, Burnette, & Scissors, 2007;Molden & Dweck, 2006;Mukhopadhyay & Johar, 2005). The use of lay theories, like other forms of implicitly held knowledge, can be triggered by features of the situational environment (Bargh, 1997;Wyer, 2004).…”
mentioning
confidence: 99%